Multiscale mechanical analysis for biomimetic implant design based on Triply Periodic Minimal Surfaces (TPMS) lattices: Application to partial replacement of femoral bone - Chrysoula Chatzigeorgiou; Boris Piotrowski; Fodil Meraghni; Yves Chemisky (Results in Engineering)
Medical implants are a common treatment for orthopedic injuries. Their apparent stiffness can be reduced by using architected internal lattices to match the gradient stiffness of the bone, thereby avoiding postoperative biomechanical problems such as stress shielding. The use of TPMS-based lattice structures with smooth junctions offers the potential to tailor the apparent modulus of an implant while minimizing stress concentration throughout the microstructure. In this study, four TPMS-based unit cells are investigated, namely: Schoen's Gyroid-like (sheet and skeletal), Schwartz's Primitive, and Schoen's IWP topologies. The objective of the investigation is to numerically replace a small region of a femoral bone, hereafter referred to as the area of interest (AoI). Multiscale approach is proposed for the 3D model of the femur. The latter consists of the global model (femur bone) and the local model (TPMS unit cell). The unit cells are selected to satisfy the elastic and mechanical loading requirements and are compared according to the von Mises stress distribution after applying periodic boundary conditions. A statistical analysis is performed and a function factor is proposed to facilitate the comparison. The developed methodology allows the design of customized and patient-specific implants when a large medical database is used due to the varying size and shape of patients' bones.